2020
DOI: 10.1063/5.0011713
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the charge carriers transport properties and electric field distribution of CH3NH3PbBr3 thick single crystals

Abstract: Below are the queries associated with your article; please answer all of these queries before sending the proof back to AIP. Article checklist: In order to ensure greater accuracy, please check the following and make all necessary corrections before returning your proof. 1. Is the title of your article accurate and spelled correctly? 2. Please check affiliations including spelling, completeness, and correct linking to authors. 3. Did you remember to include acknowledgment of funding, if required, and is it acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…Here, electronic conductivity of the measured single crystals is in the order of 10 −8 Ω −1 cm −1 . High electronic mobility has been measured using laser time-of-flight techniques in our samples μ e = 13 cm 2 V −1 s −1 , [34] in accordance with previous analysis on perovskite single crystals. [35] These mobility values allow us to infer a background carrier density n = 1.3 × 10 10 cm −3 , that also agreed with previous estimations.…”
Section: Resultssupporting
confidence: 89%
“…Here, electronic conductivity of the measured single crystals is in the order of 10 −8 Ω −1 cm −1 . High electronic mobility has been measured using laser time-of-flight techniques in our samples μ e = 13 cm 2 V −1 s −1 , [34] in accordance with previous analysis on perovskite single crystals. [35] These mobility values allow us to infer a background carrier density n = 1.3 × 10 10 cm −3 , that also agreed with previous estimations.…”
Section: Resultssupporting
confidence: 89%
“…For example, the dispersive law gives an overestimated mobility of 64 cm 2 V −1 s −1 at 7 V, while the MC simulation gives a correct description of the hole drift and mobility (21 cm 2 V −1 s −1 ) at all biases. The drift mobility found in this study is in agreement with electron (0.7-1.4 cm 2 V −1 s −1 ) [59,60] and hole (20-35 cm 2 V −1 s −1 ) [30,[61][62][63][64] mobilities found in the literature. The lower electron mobility values reported in other studies can be explained by the effect of shallow traps on electron transport, also shown in this study.…”
Section: Delaying Effect Of Traps On Holes and Electronssupporting
confidence: 92%
“…Our results demonstrate a suppressed interaction of defects and free carriers which explains the boost in stability and efficiency of singly crystal solar cells. [ 43–93 ] Further improvements in stability and conversion efficiency can be achieved by controlling shallow and deep defects, as demonstrated in this study. Special attention must be given to the collection of free electrons due to the lower electron diffusion length.…”
Section: Effect Of Defects On Optoelectronic Devices and Further Pathways Of Hybrid Perovskite Developmentmentioning
confidence: 86%
“…The value (µτ = 3.3 × 10 −3 cm 2 /V) in monocrystalline diamonds was 2−3 orders of magnitude greater than that in polycrystalline diamonds affected by carrier trapping at grain boundaries. This result indicates the high potential of monocrystalline diamonds among other candidate materials, such as high-purity germanium, microcrystalline silicon 15 , CdZnTe 16 , metal halide perovskites 17 , and h-BN 18 . However, the charge collection method returns the product of µ and τ , and these two parameters are not separable.…”
mentioning
confidence: 87%